RI 7775 Geology Of Eocene Rocks And Oil Yields Of Green River Oil Shales On Part Of Kinney Rim, Washakie Basin, Wyoming - Laurence G. Trudell (The National Institute for Occupational Safety and Health (NIOSH), 1973)
Geology and oil-yield data are presented for a 58-square-mile area encompassing the U.S. Department of the Interior oil-shale leasing program tracts in the western Washakie Basin, Sweetwater County, Wyo. Lithology and oil yields of samples from three Bureau of Mines coreholes are evaluated and correlated with Kinney Rim surface sections measured and sampled by the U.S. Geological Survey. Minable sections of oil shale averaging up to 25 gallons of oil per ton crop out on Kinney Rim in the Laney Member of the Green River Formation. Thick oil-shale sections in the Laney Member that average 15 gallons per ton represent 155 million barrels of oil in place per square mile. In the lower part of the Green River Formation the Tipton Shale Member contains a 20-to 40-foot section averaging 15 gallons per ton. Beds of high-volatile C bituminous coal up to 6 feet thick are present in intertongued parts of the lower Green River Formation and upper Wasatch Formation.